No conscientious objection without normative justification: A reply - Blackshaw, Bruce P. (Bioethics, 2019)
Benjamin Zolf, in his recent paper ‘No conscientious objection without normative justification: Against conscientious objection in medicine’, attempts to establish that in order to rule out arbitrary conscientious objections, a reasonability constraint is necessary. This, he contends, requires normative justification, and the subjective beliefs that ground conscientious objections cannot easily be judged by normative criteria. Zolf shows that the alternative of using extrinsic criteria, such as requiring that unjustified harm must not be caused, are likewise grounded on normative criteria. He concludes that conscientious objection is therefore untenable. Here, I present an alternative account, based on the value we are willing to place on conscientious objection as an expression of freedom of conscience and religion. Using an extrinsic criterion such as harm, we can make a judgement of what degree of harm should be tolerated as the cost of permitting conscientious objection. A normative criterion for judging individual claims is therefore not required.